FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN PROPERTY DAN REAL ESTATE 2019-2021 - Apriliyani, Ragil Dewi; Saharsini, Astuning (Jurnal Riset Manajemen dan Akuntansi, 2023)
The purpose of the study is to analyze the effect of the size of company, profitability, solvency, audit opinion and audit switching on audit delay in property and real estate companies in Indonesia. Quantitative methods are used in the analysis of this study.The use of purposive sampling technique leaves 35 companies from 71 populations companies, so that the total of samples in this analysis are 105 data. The research period conducted from 2019-2021. The analytical technique used in this research is descriptive statistics test, classic assumption test, multiple regression analysis and hypotesis test. The result of this study is that partially the independent variable that have an effect is the size of company, profitability and audit opinion while solvency and audit switching have no effect. Simultaneously, all independent variables have an overall effect on the dependent variable.